Hubungan antara Self-Compassion dengan Resiliensi pada Remaja Panti Asuhan Bunda Pangkalan Balai - Zaharuddin Zaharuddin; Rina Nizamia Wahyuni (Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
This study aims to determine the relationship between self-compassion and resilience in the Bunda Pangkalan Balai orphanage. This research method is correlational quantitative. The research subjects were 40 students of the orphanage who were selected using the total sample technique. The instrument used is a self-compassion scale and a resilience scale. The results of data analysis using the Pearson product moment analysis technique (SPSS ver.26 for windows) showed that there was a relationship between self-compassion and resilience in the youth at the Bunda Pangkalan Balai orphanage with a correlation coefficient I of 0.439 with a significant value of 0.022, which means the significance value is < 0.05. These results indicate that there is a relationship between self- compassion and resilience in the youth of the Bunda Pangkalan Balai orphanage. With these results, the hypothesis proposed in this study is accepted.